Manajemen Pendidikan Berbasis Community Engangement dalam Peningkatan Mutu Sekolah - Moh. Rofiki; Naufal Mubarok; Muhammad Angga (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
This research examines the role of community engagement-based education management in improving school quality. A qualitative approach with a case study was used in the research. The research location is MTs Nurul Jadid because it is easy to get data and is a superior institution within the pesantren environment. The research data consisted of primary and secondary data, each of which was obtained from research informants and scientific journals, both national and international. Data collection was carried out using three techniques, namely observation, interviews, and documentation. While data analysis was carried out in three stages, namely data reduction, data presentation, and conclusion drawing,. Community engagement-based education management for improving school quality consists of community involvement in academics, financing, and education quality.